The Biological Function Prediction of The 10-gingerol Compound of Ginger in Inhibiting Cyclooxygenase-2 Activity - Gabriella Chandrakirana Krisnamurti; Fatchiyah Fatchiyah (Chemistry Department, The University of Brawijaya, 2020)
Anti-inflammatory agents inhibit prostaglandin synthesis by blocking cyclooxygenases (COXs). The compounds extracted from ginger, 10-gingerol and 10-shogaol can inhibit inflammation but the mechanism of inhibition remains unclear. Here we used molecular docking to predict the molecular interactions between COXs and the three inhibitors, acetaminophen (CID1983), 10-gingerol (CID168115) and 10-shogaol (CID6442612). By using that acetaminophen as a gold standard, the results demonstrated that acetaminophen, 10-gingerol, and 10-shogaol could bind catalytic domain and membrane binding domain of cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2). The 10-shogaol did not show significantly different binding energy to bind to COX-1 and COX-2. The 10-gingerol posed a stronger and more specific binding to the membrane-binding domain of COX-2 than acetaminophen and 10-shogaol. The specific binding of the 10-gingerol to COX-2 could prevent the binding of the natural substrate, arachidonic acid. The results provide useful information to improving activities of anti-inflammatory.